Spis właścicieli dóbr ziemskich księstwa świdnicko-jaworskiego z 1690 roku = The 1690 census of land-owners in the Duchy of Jauer-Schweidnitz - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The 1690 census of lands and their owners is among the earliest conducted in the Duchy of Jauer-Schweidnitz during the Habsburg reign (1526-1740). Successive censuses were conductedin 1692, 1699, 1712, 1717, 1724, 1731, and 1738. After the thirty-year war, the land censuses were part of the Habsburg court's centralist policy under which coherent administration structures were built in the provinces of the Bohemian Kingdom and the very Roman Empire of the German Nation.
Keywords: Księstwo Świdnicko-Jaworskie; spis właścicieli; 17 w.